Tingkat Kepuasan Pasien Akne Vulgaris (AV) Menggunakan Krim Racikan Di Klinik Sukma Tangerang - Vini Claudya Agustine Rajagukguk; Sukmawati Tansil Tan (Lembaga Pengembangan Kinerja Dosen, 2023)
Acne vulgaris (AV) is a disease that occurs on the skin, especially in areas containing pilosebaceous, and is multifactorial. Acne vulgaris (AV) is a complex condition because it has several factors such as hormonal influences and an increase in follicle keratinization and is usually caused by microbes such as the bacterium Propionibacterium acnes (P. acnes) which is a gram-positive anaerobic commensa bacteria found on the skin. can be related to hormones and the immune system and excessive sebum production and can occur the release of inflammatory mediators. The clinical picture of acne can be seen that there are comedones, micro-comedones, open and closed comedones, sandpaper commodes, macro-comedones, missed comedones to relieve inflammation can be given a concoction of the Sukma Tangerang Clinic which is Anti-Acne Vulgaris (AV).